The relationship between off-ice and on-ice performance tests in elite adolescent male ice hockey players - Salinas, G.; Kraus, R.; Virgile, A. (The Journal of Strength and Conditioning Research, 2021)
Though specific off-ice testing has been shown to be related to on-ice hockey performance, a greater understanding of the connections between them may lead to more informative off-ice testing procedures and better overall training programs. This is particularly important for understudied populations like elite U14 ice hockey players since coaches and strength and conditioning professionals must consider their development as athletes as well as their growth and development due to age. Purpose: The purpose of this study was to investigate the relationship between off-ice and on-ice performance tests in elite adolescent male ice hockey players. Methods: Top U14 male ice hockey players from across the United States were invited to participate in a 2018 elite camp (STX 68) conducted by STX and 200 × 85. com. These athletes (n = 31, mean ± SD, age 14.36 ± 0.23 years, body mass 67.34 ± 8.19 kg) completed several off-ice performance tests including the 40-yard dash, countermovement jump (reported as distance, and subsequently converted and also reported as peak power output; PPO), broad jump, YoYo IR-2, medicine ball throw for distance, lateral bounding for distance, grip strength, pull ups, and lower body isometric dynamometry. When appropriate, tests were repeated with adequate rest to identify peak performance. On a separate day, on-ice performance tests were administered using a fully automated timing gate system with time recorded to the nearest thousandths of a second. Speed was evaluated with a 30 m forward sprint (mean ± SD, 4.34 ± 0.14 seconds) and a 30 m backward sprint (5.19 ± 0.22 seconds). The reaction test assessed reaction time and lateral agility (10.66 ± 0.50 seconds). Forward speed while challenged with multidirectional changes was evaluated with a weave agility test (without puck, 11.49 ± 0.33 seconds; with puck, 12.18 ± 0.53 seconds), while the transition test determined agility and directional change from forward to backwards skating (without puck, 12.80 ± 0.56 seconds; with puck, 13.70 ± 0.92 seconds), and both of these tests were performed once without the puck and once with the puck. Linear regression analysis was used to identify relationships between off-ice performance tests and each on-ice test. Results: The 30 m forward sprint times were significantly (p < 0.05) related to the 40-yard dash times (r = 0.59), broad jump distance (r = -0.47), countermovement jump distance (r = -0.70), and countermovement jump PPO (r = -0.44). The 30 m backward sprint times were related to the 40-yard dash times (r = 0.43; p < 0.05) as well as countermovement jump distance (r = -0.36; p < 0.05). The reaction test times were related to 40-yard dash times (r = 0.39; p < 0.05). The weave agility test times with the puck were significantly (p < 0.05) related to 40-yard dash times (r = 0.36), pull ups (r = -0.40), and the YoYo IR-2 (r = -0.43). The transition test times without the puck were related to the 40-yard dash times (r = 0.49; p < 0.05) and countermovement jump distance (r = -0.40; p < 0.05). Conclusions: Forty yard dash performance was significantly related to some version of all of the on-ice performance tests. Countermovement jump results were also significantly related to several on-ice performance tests. Practical Applications: These data indicate that coaches should consider utilizing off-ice sprint as well as vertical and horizontal jump tests with elite U14 male ice hockey players as they focus on the development of lower body power through specific off-ice training.